Prevalence of Depressive Symptoms among Medical Students of Faculty of Medicine, Derna - Serag Almzainy,; Amal Srgewa, (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Anxiety, fear, and depression significantly impact the academic performance and overall well-being of medical students, especially those facing multiple stressors. In Derna, Libya, students have confronted civil unrest challenges compounded by the COVID-19 pandemic. Recognizing the prevalence of depressive symptoms among these students is paramount. This study represents the inaugural investigation in Derna, aiming to evaluate depression prevalence among Faculty of Medicine students. Methods. A cross-sectional study conducted at Derna University from August 17 to 30, 2022, involved medical students across all academic years. The Patient Health Questionnaire-9 (PHQ-9) assessed depressive symptoms, categorizing scores ≥ 15 as indicative of moderately severe to severe depression. Statistical analyses, including chi-square and Spearman correlation tests, analyzed the collected data. Results. About 262 students participated, revealing that 28.6% had a PHQ score ≥ 15, denoting moderate to severe depression, with 24.1% reporting suicidal thoughts. Depression exhibited significant associations with students' family mean monthly income (P=0.02) and their preferences concerning attending lectures or studying solely from home (P=0.012). Conclusion. The findings underscore a critical need for tailored mental health services and support programs targeting the well-being of medical students. Implementing dedicated measures, involving academic mentors and medical tutors, is imperative to effectively support these students. This study emphasizes the urgency of prioritizing mental health resources and strategies to alleviate the burden of depression among medical students in Derna, Libya, ensuring their academic success and overall well-being.